Prophylactic cranial irradiation may impose a detrimental effect on overall survival of patients with nonsmall cell lung cancer: a systematic review and meta-analysis. - Shuan-shuan Xie; Ming Li; Cai-cun Zhou; Xiao-lian Song; Chang-hui Wang (PLoS ONE)
Purpose To determine the role of brain metastases (BM) and overall survival (OS) in patients with non-small cell lung cancer (NSCLC) by performing a meta-analysis of the RCTs (randomized controlled clinical trials) and non-RCTs (non-randomized controlled clinical trials) published in the literature. Methods A meta-analysis was performed using trials identified through PubMed, EMBASE and Cochrane databases. Two investigators independently assessed the quality of the trials and extracted data. The outcomes included BM, OS, median survival (MS), response rate (RR), Hazard ratios (HRs) and odds ratios (ORs), and their 95% confidence intervals (CIs) were pooled using ReMan software. Results Twelve trials (6 RCTs and 6 non-RCTs) involving 1,718 NSCLC patients met the inclusion criteria. They were grouped on the basis of study design for separate Meta-analyses. The results showed that prophylactic cranial irradiation (PCI) reduced the risk of BM as compared with non-PCI in NSCLC patients (OR = 0.30, 95% [CI]: 0.21-0.43, p<0.00001). However, HRs for OS favored non-PCI (HR = 1.19, 95% [CI]: 1.06-1.33, p = 0.004), without evidence of heterogeneity between the studies. Conclusion Our results suggest that although PCI decreased the risk of BM, it may impose a detrimental effect on OS of NSCLC patients.